Penegakan Hukum: Kendaraan Bermotor yang Dimodifikasi dalam Peraturan Lalu Lintas Angkutan Jalan - Fajar Agung Wahyudi; Muhyi Mohas (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2023)
From a legal perspective, modifications to motorized vehicles must adhere to existing rules and regulations to ensure the legal certainty and legitimacy of vehicle owners. A prevalent issue in the Serang region is the phenomenon of public workshops modifying vehicles without obtaining recommendations from a brand holder representative. This study addresses two primary questions: First, how does the Serang Resort Police enforce criminal legislation against goods transport companies that modify vehicles in line with Act Number 22 of 2009 on Traffic and Road Transportation in the Serang Resort Police area? Second, what is the criminal responsibility of goods transport companies that modify vehicles according to the standards set by the Serang Resort Police based on Act 22 of 2009 on Road Traffic and Transportation? Utilizing a normative juridical method with a statute-based approach, the research findings indicate that effective law enforcement is contingent upon three key elements: legal structure, legal substance, and legal culture, all interrelated. Due to freight forwarders' non-compliance with rules and regulations, criminal responsibility is warranted under the principles of strict liability and vicarious liability. The study concludes that there is a lack of optimal synergy in law enforcement for traffic and road transport crimes among the Serang Resort Police, Department of Land Transportation Serang District, and The Land Transportation Management Center VIII. Additionally, there are legal gaps in the Road Transportation Traffic Law, including regulations for corporations, general workshops for business actors, the application of maximum criminal sanctions, and protection for freight transportation. Issues such as a culture of bribery, selective prosecution, a lack of legal knowledge among human resources, and abuse of power for personal or group interests further complicate the situation. The study emphasizes criminal liability, focusing on elements of error based on the concepts of strict liability and vicarious liability